Echinometra mathaei and its ectocommensal shrimps: the role of sea urchin spinochrome pigments in the symbiotic association. Issue 1 (December 2018) - Brasseur, Lola; Caulier, Guillaume; Lepoint, Gilles; Gerbaux, Pascal; Eeckhaut, Igor
Abstract Tuleariocaris holthuisi andArete indicus are two ectocommensal shrimps closely associated with the tropical sea urchinEchinometra mathaei . This study provides a comparison of these twoE .mathaei symbiotic crustaceans and particularly focuses on the relationship betweenT .holthuisi and its host's pigments (i.e. spinochromes), and its dependency on its host. While all the analyses underline a close association betweenA .indicus andE .mathaei, they reveal a particularly close interaction betweenT .holthuisi and its host. Chemical analyses reveal that these shrimps present the same spinochrome composition asE .mathaei, and have similar colouration, allowing camouflage. Isotopic composition and pigment loss after host separation suggest that these pigments are certainly assimilated upon feeding on the urchin. Moreover, symbiont isolation experiments demonstrate the high dependency ofT .holthuisi on its host and the importance of the host's pigments on their survival capacity. Finally, some host recognition mechanisms are investigated forT .holthuisi and show the probable implication of spinochromes in host selection, through chemical recognition. Hence, all the results suggest the essential roles of spinochromes forT .holthuisi, which, in turn, suggests the potential implication of these pigments in the shrimps' metabolism.